A Cultural Perspective on Entrepreneurship: A Case Study of Sports Entrepreneurship Management Strategies in China - Xiaohui Dong, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The cultural perspectives in sports entrepreneurship management involve tailoring strategies to the unique cultural contexts of sports, taking into account cultural traditions, values, and societal norms to foster the successful development of businesses. This research aims to analyse the cultural perspectives of entrepreneurship and the management strategies of sports entrepreneurship in China. The study yielded a total of 490 usable responses. In addition, we provided an explanation of the selection criteria and utilised SPSS for analysis. Our findings focus on assessing sports entrepreneurship management and surveying the perspective of entrepreneurship culture. Lastly, it examines the cultural viewpoint of entrepreneurship and strategies for managing sports entrepreneurship. Insights from culture enhance sports entrepreneurship by transforming management strategies, emphasising flexibility, diversity, and leveraging cultural nuances to foster innovation and sustained achievement in the sports industry.